2012
DOI: 10.1007/s10831-012-9092-9
|View full text |Cite
|
Sign up to set email alerts
|

A cross-linguistic study of Taiwanese tone perception by Taiwanese and English listeners

Abstract: The present study investigated tone perception by speakers of Taiwanese Southern Min and those of American English with an AX discrimination task. Two Taiwanese Southern Min tone continua were constructed from natural speech stimuli. One continuum ranged from a high level tone (T55) to a mid level tone (T33), and the other from a high level (T55) to a high falling tone (T51). The results showed that perception by Taiwanese listeners was quasi-categorical for the contour-level tone continuum but mostly continuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 43 publications
(76 reference statements)
3
14
1
Order By: Relevance
“…In apparent contrast with previously published investigations on lexical-tone discrimination (e.g., Burnham and Francis, 1997;Hall e et al, 2004;Sun and Huang, 2012), both French-and Mandarin-speaking listeners were able to correctly perceive differences in pitch contours with the present lexical tones. The absence of difference between language groups results from a ceiling effect (that is from the high performance of both groups for the current discrimination task and for the present speech stimuli that were carefully selected from a large set of clearly articulated utterances).…”
Section: Discussioncontrasting
confidence: 99%
“…In apparent contrast with previously published investigations on lexical-tone discrimination (e.g., Burnham and Francis, 1997;Hall e et al, 2004;Sun and Huang, 2012), both French-and Mandarin-speaking listeners were able to correctly perceive differences in pitch contours with the present lexical tones. The absence of difference between language groups results from a ceiling effect (that is from the high performance of both groups for the current discrimination task and for the present speech stimuli that were carefully selected from a large set of clearly articulated utterances).…”
Section: Discussioncontrasting
confidence: 99%
“…Four natural T1–T4 pairs were recorded. To avoid a ceiling effect due to the high acoustic salience of the T1–T4 contrast (Huang and Johnson 2010; Sun and Huang 2012; Liu and Kager 2014), an acoustically contracted contrast was created from a T1–T4 tonal contrast by manipulating the F0 direction via the software PRAAT (Boersma and Weenink 2010) to reduce the acoustic salience of the contrast. Four interpolation points along the pitch contours (at 0, 33, 67, and 100%) were introduced.…”
Section: Methodsmentioning
confidence: 99%
“…Existing research on the perception of lexical tones suggests that native Mandarin listeners perceive Mandarin tones categorically, with listeners relying primarily on pitch contour differences to distinguish the tones (Burnham & Mattock, 2007;Hallé, Chang, & Best, 2004;Sun & Huang, 2012;Wang, 1976). For instance, using identification and discrimination tasks, Wang (1976) found that Mandarin listeners showed the typical pattern of categorical perception when perceiving a dynamic tonal continuum varying from a level tone (T1) to a rising tone (T2); that is, listeners showed steep slopes at the category boundary in their categorization function and marked peaks at the category boundary in their discrimination function.…”
Section: Introductionmentioning
confidence: 99%